2019
DOI: 10.1186/s13073-019-0638-6
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular and pharmacological modulators of the tumor immune contexture revealed by deconvolution of RNA-seq data

Abstract: We introduce quanTIseq, a method to quantify the fractions of ten immune cell types from bulk RNA-sequencing data. quanTIseq was extensively validated in blood and tumor samples using simulated, flow cytometry, and immunohistochemistry data. quanTIseq analysis of 8000 tumor samples revealed that cytotoxic T cell infiltration is more strongly associated with the activation of the CXCR3/CXCL9 axis than with mutational load and that deconvolution-based cell scores have prognostic value in several solid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
811
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 994 publications
(818 citation statements)
references
References 65 publications
7
811
0
Order By: Relevance
“…By running ESTIMATE on TCGA RNA-seq data, the stromal and immune score of each sample can be estimated as previously described [90][91][92]. We quantified the proportion of cells that belonged to each of 10 immune cell types (B cells, M1 macrophages, M2 macrophages, monocytes, neutrophils, NK cells, CD4+ T cells, CD8+ T cells, regulatory T cells, and dendritic cells) using the quanTIseq package in R [93]. CMS classifications of COAD were performed using the CMSCaller package in R [64].…”
Section: Estimation Of Tumor Cellular Components and Crc Subtypesmentioning
confidence: 99%
“…By running ESTIMATE on TCGA RNA-seq data, the stromal and immune score of each sample can be estimated as previously described [90][91][92]. We quantified the proportion of cells that belonged to each of 10 immune cell types (B cells, M1 macrophages, M2 macrophages, monocytes, neutrophils, NK cells, CD4+ T cells, CD8+ T cells, regulatory T cells, and dendritic cells) using the quanTIseq package in R [93]. CMS classifications of COAD were performed using the CMSCaller package in R [64].…”
Section: Estimation Of Tumor Cellular Components and Crc Subtypesmentioning
confidence: 99%
“…A description of all methods is provided in Table 1 and Additional file 1: Table S2. First, while the Spearman correlations between microscopic (red) and all methylomic (blue) or transcriptomic (green) estimates were poor to moderate, our analysis showed that stromal infiltration correlates better [20]; digTMA, tissue microarray scored by Visiopharm (digital analysis); MCP, MCP-counter [22]; meTIL, methylation TIL score [27]; metCBS, methylCIBERSORT [25]; itTIL, intra-tumoral TIL on H&E; qSEQ, quanTIseq [21]; sTIL, stromal TIL on H&E; TILrna, TIL score based on transcriptome [26]; TMA (H&E), sTIL scored on TMA; TMA (IHC), tissue microarray scored by pathologists with CD3 and CD20 markers to calculate the sTIL; WS (IHC), whole slide immunohistochemistry of CD3 and CD20 by pathologists with all other methods, including transcriptomic and methylomic methods, as compared to the intra-tumoral infiltration (Fig. 3a).…”
Section: Comparison Of Microscopic Transcriptomic and Methylomic Evmentioning
confidence: 77%
“…Finally, of the methods that predict global immune infiltration based on the transcriptome (green label in Fig. 3a), TILrna showed the highest correlations with the various immune gene signatures (pink label, r = 0.90-0.94), while quanTIseq [21] showed the poorest correlations (r = 0.16-0.18). Similar analyses were further carried on separately for ER-negative and ER-positive tumors as the biological significance of the immune infiltrate may be different [46,47] (Fig.…”
Section: Comparison Of Microscopic Transcriptomic and Methylomic Evmentioning
confidence: 99%
“…However, the effort was limited to available knowledge from cell type profiling in vitro and in bulk [28][29][30]37] , and does not account for all cell-type specific expression differences, particularly where the differences in miRNA expression levels are more subtle or unknown. Cell deconvolution of bulk tissue sequencing data based on gene expression is in itself a large and rapidly developing field [79][80][81] . As of yet, development of rigorous miRNA expression profiles on the cellular level is still in its infancy [82] .…”
Section: Resultsmentioning
confidence: 99%